9
$\begingroup$

Is there a general way to find the $q > 0$ solving the equation from the geometric series $$1+q+q^2+q^3+\ldots + q^n = a$$ or $$\frac{1-q^{n+1}}{1-q} = a\quad\text{with } q \neq 1$$ for $a > 1$ and $n\in\mathbb N$?


My thoughts: Since polynomials aren't solvable in general for degree 5 or higher, I guess the above equation has no explicit solution for $n\ge 5$. In this case numerical approximations can be used. For $n=5$ also this method can be used.

$\endgroup$
  • 4
    $\begingroup$ It is easier to solve $\frac{q^{n+1}-1}{q-1}=a$ $\endgroup$ – Peter Aug 25 '16 at 12:37
  • 3
    $\begingroup$ Newton's method is often used for this case. For $a$ close to $1$, $q\approx a-1$ and for $a\gg1$, $q\approx\sqrt[n]a$. $\endgroup$ – Yves Daoust Aug 25 '16 at 12:42
  • 1
    $\begingroup$ Sorry, I meant $q\approx1-1/a$, not $1-a$. $\endgroup$ – Yves Daoust Aug 25 '16 at 12:49
  • 1
    $\begingroup$ For a numerical method, I wrote $a(q-1) = q^{n-1} - 1 = \int_1^q (n+1)x^n \; dx$ and then chose a $k$ and approximated the integral with trapezoid or Simpson's rule. I ended up with $a(q-1) \approx (n+1)q^{n+1}F(k)/3k^{n+1}$. Where $F(k)$ is not that hard to work out once $k$ is chosen. This near equation is only slightly easier to solve than the original, but I offer my thoughts. $\endgroup$ – B. Goddard Aug 25 '16 at 13:17
  • 1
    $\begingroup$ You can find a series solution here: arxiv.org/abs/math/9411224 $\endgroup$ – N74 Aug 26 '16 at 11:32
1
$\begingroup$

Re-arrange \begin{align*} q &= \frac{a-1}{a-q^n} \\ &= \frac{a-1}{a-\left(\frac{a-1}{a-q^n}\right)^n} \\ &= \frac{a-1} {a-\left( \frac{a-1} {a-\left( \frac{a-1}{a-\ddots} \right)^n} \right)^n} \\ &= \frac{a-1}{a} \left \{ 1+\frac{(a-1)^n}{a^{n+1}}+\ldots+ \frac{(nk+k)!}{k! (nk+1)!} \left[ \frac{(a-1)^n}{a^{n+1}} \right]^{k}+\ldots \right \} \end{align*}

Lagrange inversion formula

\begin{align*} f(q) &= aq-q^{n+1} \\ q &= f^{-1}(a-1) \\ &= \sum_{i=1}^{\infty} \frac{1}{i!} \frac{d^{i-1}}{dx^{i-1}} \left. \left(\frac{x-0}{f(x)-f(0)} \right)^{i} \right|_{x=0} [(a-1)-f(0)]^{i} \\ &= \sum_{i=1}^{\infty} \frac{1}{i!} \frac{d^{i-1}}{dx^{i-1}} \left. \left(\frac{1}{a-x^{n}} \right)^{i} \right|_{x=0} (a-1)^{i} \end{align*}

$\endgroup$
  • $\begingroup$ Can you better explain your last equivalence. It seems interessino but I can't see how to make it general. $\endgroup$ – N74 Aug 26 '16 at 11:35
  • $\begingroup$ $$q=\frac{a-1}{a}+\delta=\frac{a-1}{a-\left( \frac{a-1}{a}+\delta \right)^{n}} \implies \frac{a-1}{a}+\delta=\frac{a-1}{a} \left[ 1+\frac{1}{a}\left( \frac{a-1}{a}+\delta \right)^{n}+\ldots \right] $$$$\implies \delta \approx \frac{(a-1)^{n+1}}{a^{n+2}}$$ and repeat in similar manner to obtain higher order terms. $\endgroup$ – Ng Chung Tak Aug 26 '16 at 12:38
  • $\begingroup$ See also Lagrange Inversion Formula $\endgroup$ – Ng Chung Tak Aug 26 '16 at 12:54

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.